ORUBEEX WRAP: Innovation in food packaging based on beeswax and corn husk waste (Zea mays L.) as an eco-friendly solution - Azrial, Fahmi; Saputra, Agong; Rahmawati, Eliza Khusnul Dewi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The urgent issue of plastic waste has driven innovation in eco-friendly packaging. ORUBEEX WRAP emerges as a solution by utilizing beeswax and corn husk waste (Zea mays L.) to replace single-use plastic packaging. Beeswax is chosen for its biodegradable, reusable, and antimicrobial properties, while corn husk waste is used as a filler to enhance mechanical strength and flexibility. This innovation not only reduces environmental impact but also supports the circular economy by transforming agricultural waste into value-added products. Methods: This study employs a descriptive-analytical approach, collecting and analyzing data from literature studies, scientific journals, and trusted sources related to beeswax, corn husk waste, and eco-friendly packaging. The writing process includes data collection, analysis of raw material potential, and evaluation of the environmental and economic impacts of ORUBEEX WRAP. Findings: ORUBEEX WRAP offers key advantages as a biodegradable and reusable packaging solution that can reduce plastic waste. The antimicrobial properties of beeswax help extend food shelf life, while the utilization of corn husk waste provides economic value to farmers. However, the product faces limitations in mechanical durability and application to wet or oily foods, as well as relatively high initial production costs. Conclusion: ORUBEEX WRAP is a sustainable innovation combining the benefits of beeswax and corn husk waste to reduce reliance on single-use plastics. Despite technical and economic challenges, the product holds significant potential to promote eco-friendly practices and the circular economy. Novelty/Originality of this article: The originality of ORUBEEX WRAP lies in its innovative combination of beeswax and corn husk waste, which has not been extensively explored in the food packaging industry. This innovation not only offers an eco-friendly solution but also utilizes previously neglected agricultural waste, creating economic value and supporting sustainability principles.